Intrasplenic hepatocyte transplantation in rats: A preliminary report - Gürden GÜR; Didem KARAVELİOĞLU and Banu BİLEZİKÇİ and; ilmi ÇEKİN and Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-